PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN INFRASTRUKTUR JALAN TANI DESA TETEAJI KECAMATAN TELLU LIMPOE KABUPATEN SIDENRENG RAPPANG - Adam Latif; Muhammad Rusdi; Dedi Setiawan (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
This study aims to find out how community participation in the village of Teteaji, how the construction of farm road infrastructure in the village of Teteaji, and how community participation in the construction of farm road infrastructure. The population in this study was 384 farming communities where the sampling used was Simple Random Sampling, with Simple Random Sampling techniques with a total sample of 79 farming communities, this study used a Quantitative Descriptive Method. Data collection techniques are used through observation, questionnaires, and library studies. Data analysis techniques used are frequency tabulation analysis, and linear regression analysis using SPSS 21.0 for windows.The results of this study indicate that the average percentage of community participation in Teteaji Village was 61.6% in the good category and the construction of farm road infrastructure in the Teteaji Village was 70.2% in the good category. To find out the magnitude of the effect of community participation on the construction of farm road infrastructure in Teteaji Village, Tellu Limpoe District, Sidenreng Rappang Regency, namely by looking at the value of R2 or R square. The results from the Model Summary table, in this section, the value of R = 0.896 and the coefficient of RSquare determination or R2 are 0.955. This shows that the construction of farm road infrastructure is 89.6% due to community participation while the remaining 10.4% is due to other factors not examined.